Javanese Ethical Values in Tafsir Al-Huda - Novita Siswayanti (Analisa: Journal of Social Science and Religion, 2013)
Tafsir Al-Huda, interpreting Quran in Javanese language, is one of Indonesia interpretation in which the context projecting the process of mingle between Quran and Javanese culture heritage owned by the author with social culture condition surrounded. Tafsir Al-Huda is a guidebook for experiencing sacred messages of Quran which is filled with moral values of Javanese culture. This research tried to study Javanese ethical values written in Tafsir Al-Huda. Content analysis method with hermeunetic approach is used in this study by interpreting symbols in form of text in order to find its meaning. This research conclude that Tafsir Al-Huda has Javanese cultural perspective, use cultural context, and has acomodating and integrating interconection.  Tafsir Al-Huda embody the Javanese philosophy and view of life to make society remember the God and be aware to any behavior and saying (eling lan waspada), tolerate and respect others (tepa selira), and live in harmony with the concept that harmony can create unity, dispute can create separation (rukun agawe santosa lan crah agawe bubrah).